A method for calculating gas hydrate saturation by dual parameters of logging - Li, Haiyan; Liu, Jundong; Qu, Cuixia; Song, Hongye; Zhuang, Xueliang (Frontiers in Earth Science, 2022)
Natural gas hydrates occur in geological environments with special conditions and have physical properties completely different from those of oil and gas, resulting in low accuracy of saturation values calculated by conventional Archie formula or the sonic velocity method. In order to obtain the reliable saturation value of natural gas hydrate, a two-parameter calculation model of resistivity and acoustic interval transit time based on logging data is established by analyzing the logging response characteristics. Comparing the saturation results calculated by the two-parameter calculation model with the core experiment results, the average relative error of the results calculated by the model is 7 %, and the average relative error of the results calculated by the conventional Archie formula is 24 %. The results of the former were significantly better than those of the latter, indicating that the logging two-parameter model effectively improves the calculation accuracy of gas hydrate saturation. The saturation calculation model is based on objective theory and has wide adaptability, which provides a reliable basis for hydrate resource evaluation and exploration and development in the study area.